2021
DOI: 10.7150/ijms.50916
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutation Profiling of Papillary Thyroid Carcinomas by Whole-exome Sequencing and Its Relationship with Clinical Characteristics

Abstract: The incidence of papillary thyroid carcinomas (PTCs) has increased rapidly during the past several decades. Until now, the mechanisms underlying the tumorigenesis of PTCs have remained largely unknown. Next-generation-sequencing (NGS) provides new ways to investigate the molecular pathogenesis of PTCs. To characterize the somatic alterations associated with PTCs, we performed whole-exome sequencing (WES) of PTCs from 23 Chinese patients. This study revealed somatic mutations in genes with relevant functions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Extracellular signal-regulated kinase (ERK) and nuclear factor kappa B (NF-κB) also play essential roles in many biological processes, such as cell growth, tumorigenesis and autophagy and apoptosis [ 39 42 ]. More importantly, in a previous study, the BRAF V600E mutant notably activated the MAPK signaling pathway in BRAF-mutant thyroid cancers [ 43 , 44 ]. In this study, RNA sequence revealed that WT1 is closely associated with PI3K/AKT signaling network, mTOR signaling cascades, MAPK signaling pathway and NF-kappa B signaling pathway.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Extracellular signal-regulated kinase (ERK) and nuclear factor kappa B (NF-κB) also play essential roles in many biological processes, such as cell growth, tumorigenesis and autophagy and apoptosis [ 39 42 ]. More importantly, in a previous study, the BRAF V600E mutant notably activated the MAPK signaling pathway in BRAF-mutant thyroid cancers [ 43 , 44 ]. In this study, RNA sequence revealed that WT1 is closely associated with PI3K/AKT signaling network, mTOR signaling cascades, MAPK signaling pathway and NF-kappa B signaling pathway.…”
Section: Discussionmentioning
confidence: 97%
“…Then, the cells were placed in 4% paraformaldehyde for approximately 30 min, and then, 0.03% Triton X-100 was added and incubated for 20 min. The manufacturer’s protocol for the immunofluorescence assay was followed as previously described [ 44 ]. The images were analyzed by a fluorescence microscope and ImageJ software (Version 1.8.0).…”
Section: Methodsmentioning
confidence: 99%
“…The activation of the ABL tyrosine kinases was also detected in breast, colon, lung, kidney and melanomas ( Greuber et al, 2013 ). Although this mutation has been reported to have a high prevalence in PTC patients, its role in PTC is yet to be determined ( Qi et al, 2021 ). Whether there is an effect of BCR -rs372013175 in gene fusion process between BCR and ABL , remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…PTCs are inert and one of the cancers with the lowest mutation density. BRAF V600 is the most common and specific genetic alteration in PTC [ 113 , 114 ]. FTC accounts for about 5% of thyroid cancer.…”
Section: Application Of Single-cell Sequencing In the Diagnosis And T...mentioning
confidence: 99%